A retrospective study on the physical growth of twins in the first year after birth - Pan, Ting; Huang, Yanru; Cheng, Qian; Chen, Li; Hu, Yan; Dai, Ying; Liu, Xiao; Jiang, Zhiyang; Zhong, Yuanfeng; Zhang, Zhanzhan; Chen, Qian; Zhang, Qian; et al. (Frontiers in Nutrition, 2023)
Objectives: This study analyzed the physical growth of small for gestational age (SGA) and appropriate for gestational age (AGA) in twins up to one year after birth. Methods: Weight, length and head circumference data of 0-1-year-old twins were collected from Child Health Care System from 2010 to 2019. Physical data were presented as Z scores.Five parameters, growth level of weight, body length and head circumference, growth velocity, the proportion of body (weight by stature) were compared in twins.Results: Three thousand nine hundred and nine cases were collected (22.61% SGA, 77.39% AGA). 1.In both groups, WAZ (Weight-for-age z-score), HCZ (Head circumference-for-age z-score), and LAZ (Length-for-age z-score) increased more rapidly in the first 6 months. By the age of one, WAZ, HCZ, LAZ reached the normal range but none had reached the average level of normal singleton children. 2. The mean of WAZ, HCZ and LAZ in AGA group were between -1 to 0, and between -2 to -1 in SGA group in the first year after birth. The SGA group lagged significantly behind the AGA group. The LAZ of SGA and AGA was lower than WAZ and HCZ. 3. The proportion of preterm AGA was the largest in twins, and the growth rate of preterm AGA was the fastest. Preterm twins had greater growth potential than term twins. However, the growth level of preterm SGA was always low. 4. The WFLZ(Weight-for-length z-score) in each group was approximately (close to 0) . WFLZ of SGA is smaller than that of AGA at most time points. After 4 months of age, the WFLZ in twins had a downward trend. The WFLZ of preterm SGA approaching -1 at about 1 year old., in order to provide a reference for early feeding.Conclusion: The physical growth of SGA and AGA in twins in the first year can reach the normal range but can't reach the average level of normal singleton children. More attention should be paid to SGA in twins, especially preterm SGA. We should give proper nutrition guidance after 4 months of age to ensure the appropriate weight by stature of SGA in twins.